The militia movement : fighters of the far right - Sonder, Ben, 1954- (New York : F. Watts, 2000)
Discusses the history and philosophies of the far-right militia movement and its connections with hate groups and domestic terrorism.
Includes bibliographical references (p. 120) and index.
Keywords: Militia movements -- United States; Terrorism -- United States; Government, Resistance to -- United States; Hate groups -- United States; Right-wing extremists -- United States